2021
DOI: 10.1208/s12248-021-00600-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved Decision-Making Confidence Using Item-Based Pharmacometric Model: Illustration with a Phase II Placebo-Controlled Trial

Abstract: This study aimed to illustrate how a new methodology to assess clinical trial outcome measures using a longitudinal item response theory–based model (IRM) could serve as an alternative to mixed model repeated measures (MMRM). Data from the EXACT (Exacerbation of chronic pulmonary disease tool) which is used to capture frequency, severity, and duration of exacerbations in COPD were analyzed using an IRM. The IRM included a graded response model characterizing item parameters and functions describing symptom-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…A median relative sample size over the 4-week intervals of 4.0 (FF/UMEC/VI) and 4.9-fold (BUD/FOR) larger would have been required for the MMRM analysis to achieve the IRT precision. These values are comparable with a 3.5-fold smaller study size with IRT compared to MMRM analysis using RS-Total data from a Phase II trial ( 24 ). This is particularly important in cases where a large number of patients cannot be recruited for pivotal trials (e.g.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…A median relative sample size over the 4-week intervals of 4.0 (FF/UMEC/VI) and 4.9-fold (BUD/FOR) larger would have been required for the MMRM analysis to achieve the IRT precision. These values are comparable with a 3.5-fold smaller study size with IRT compared to MMRM analysis using RS-Total data from a Phase II trial ( 24 ). This is particularly important in cases where a large number of patients cannot be recruited for pivotal trials (e.g.…”
Section: Discussionsupporting
confidence: 73%
“…Using data from a Phase III study, a longitudinal IRT improved the precision in the efficacy endpoint compared to MMRM. The use of NLME analysis based on item-level data (IRT) was recently proposed as an alternative to MMRM for evaluation of efficacy in the analysis of data from a Phase II study, where IRT improved the precision of the estimated drug effect considerably in comparison to MMRM ( 24 ). The benefits of using an IRT over other statistical methods such as least-square mean analysis have already been demonstrated, highlighting its higher power to detect a drug effect ( 13 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of IRT‐based analysis versus total score analysis of clinical trial data has already been demonstrated by studies using both empirical and simulation data to show that estimation of the treatment effect is less biased when applying IRT 6,7 . IRT has also increasingly been applied in the field of nonlinear mixed effects (NLME) modeling, where longitudinal models describing disease progression and treatment effect are now developed based on the change in ψ over time instead of the total score 3,8–14 . Many of these studies have shown that the statistical power to determine treatment effect using an IRT approach is higher when compared to using the total score data in NLME modeling 9,10,13 .…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 IRT has also increasingly been applied in the field of nonlinear mixed effects (NLME) modeling, where longitudinal models describing disease progression and treatment effect are now developed based on the change in ψ over time instead of the total score. 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 Many of these studies have shown that the statistical power to determine treatment effect using an IRT approach is higher when compared to using the total score data in NLME modeling. 9 , 10 , 13 These studies either used hypothetical questionnaires for simulations or were based on data from questionnaires used in clinical practice, such as the State Trait Anxiety Index Dutch Y‐version (STAI‐DY), the Exacerbation of Chronic Pulmonary Disease Tool (EXACT), the Unified Parkinsons Disease Rating Scale (UPDRS), and Hamilton depression rating scale (HAMD‐17).…”
Section: Introductionmentioning
confidence: 99%